2021
DOI: 10.1037/neu0000729
|View full text |Cite
|
Sign up to set email alerts
|

Examining cognitive speed and accuracy dysfunction in youth and young adults with pediatric-onset multiple sclerosis using a computerized neurocognitive battery.

Abstract: Objective: We evaluated performance on the Penn Computerized Neurocognitive Battery (PCNB), a tool assessing accuracy and response time across four cognitive domains, alongside the Symbol Digit Modalities Test (SDMT), a measure of processing speed commonly used in MS. We determined whether performance decrements are more likely to be detected on measures of accuracy versus response time in pediatric-onset multiple sclerosis (POMS). Methods: Performance on the SDMT, accuracy on PCNB tests belonging to four doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…This suggested that the prolongation of reaction time might be a result of an effort to reduce the rate of error. Previous studies also supported that SRTT results indicated longer reaction times in patients with MS and that this difference became further manifest with increased severity of disease (18)(19)(20)(21)(22). Previous studies on memory in patients with MS generally reported impaired memory (23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 55%
“…This suggested that the prolongation of reaction time might be a result of an effort to reduce the rate of error. Previous studies also supported that SRTT results indicated longer reaction times in patients with MS and that this difference became further manifest with increased severity of disease (18)(19)(20)(21)(22). Previous studies on memory in patients with MS generally reported impaired memory (23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, the study showed an association between higher IQ and older age at disease onset, shorter MS duration and lower EDSS. Using a computerized neurocognitive battery, a more recent study demonstrated reduced accuracy on tests of attention/inhibition, visuospatial processing working memory and verbal memory (after adjusting for response time), in adolescents and young adults with POMS, compared with healthy control [ 26 ]. On the other hand, the absence of significant differences between cognitive performances among pediatric patients compared with a control healthy group was described in a recent study by Krupp et al [ 27 ].…”
Section: Resultsmentioning
confidence: 99%